(untitled) (Global Journal of Human-Social Science, 2020)
Malaysian healthcare is nominated as one of the best healthcare providers in the world. However, does this fact reflect the patients’ satisfaction? Therefore, this research aims to investigate whether empathy, competency, and service quality influence patients’ satisfaction in healthcare services in Selangor, Malaysia. Primary data are collected using a self-administered questionnaire and a sample of 206 patients from four government and private hospitals in Selangor. Data were analysed through descriptive statistics, correlation and regression analysis. The findings show that empathy has the strongest relationship (β= .403) followed by service quality with (β=.284) and competency (β= .176). All factors also influenced patients’ satisfaction. All identified variables contribute to a big amount of variances (R 2 =66.8percent) to the overall hospital performance that makes its client happy and satisfied. The understanding patients’ satisfaction will lead to many improved services. Practically, this study can contribute to a better experience for patients and knowledge for hospitals to strive for a better service healthcare provider.